Case report: A case of pulmonary mucormycosis caused by Rhizopus azygosporus infection complicated by type 2 diabetes mellitus - Wang, Lu; Qu, Yuanqing; Tang, Lu; Li, Yanmei; Liu, Lu; Liu, Yuan (Frontiers in Medicine, 2023)
A case of pulmonary mucormycosis (PM) caused by Rhizopus azygosporus infection complicated with type 2 diabetes mellitus was reported. The adult male patient experienced a productive cough for more than 10 days and aggravated with blood in his sputum for 9 days. Laboratory examination confirmed that he had type 2 diabetes mellitus and diabetic ketosis for more than 3 years, and his chest computed tomography (CT) showed lesions, cavities, and a little effusion in the right lower lobe. The lavage fluid was taken by bronchoscope for bacterial culture and mNGS, which indicated Rhizopus azygosporus growth. Mucormycosis was diagnosed. The patient was given amphotericin B cholesterol sulfate complex for 30 days, and his renal function was closely monitored. After that, his right lower lobe was resected. Up to now, the patient has recovered well.